If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2p + -1(-10) + 7p = -5 Multiply -1 * -10 -2p + 10 + 7p = -5 Reorder the terms: 10 + -2p + 7p = -5 Combine like terms: -2p + 7p = 5p 10 + 5p = -5 Solving 10 + 5p = -5 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5p = -5 + -10 Combine like terms: 10 + -10 = 0 0 + 5p = -5 + -10 5p = -5 + -10 Combine like terms: -5 + -10 = -15 5p = -15 Divide each side by '5'. p = -3 Simplifying p = -3
| c+150=1750 | | -3b-4-3=5 | | 6y-10y-11=8y-2y+29 | | 0.9x-0.3(8-5x)=-0.4(x-8) | | -4(3y-9)-y=4(y-3)fory | | 0.3x-0.2=0.01 | | -(2m+11)x=-3m-21 | | -4x+3(10-6)=60 | | 5/4=-x/16 | | -0.8a-8=0.3a | | (9s+4)(5s-15)=0 | | 18=-9/2x | | 0.6(8x+5)=0.1-(x-3) | | -4(3y-9)-y=4(y-3) | | -16t^2+120t+56=0 | | -31/2x=3 | | (2x-4)/39=24/(x-6) | | y=36cos(x) | | 7(x+3)=5x+13 | | 2/3n-5/8=7/8 | | 2.4=(3m+4) | | x/2(28-x)-96=0 | | g(3)=9 | | 0.2(x+3)-0.4(x+3)=0.2x-0.6 | | m-64.5=-7.1 | | 64b^3+1=0 | | -27=-253+x | | 13(t-3)+5t=6(3t+5)-8 | | 2/3g=4/9 | | 0=x^3+3x^2-24x-30 | | 28x^2-x-2=0 | | 5x-4=8y-3 |